INVESTIGATION OF SOILS IN PERMANENTLY ANTHRAX-CONTAMINATED AREAS IN THE REPUBLIC OF ALTAI AND THE ALTAITERRITORY - Галина Хамроевна Базарова; Наталья Валентиновна Лукьяненко; Зоригма Федоровна Дугаржапова; Валерий Владимирович Шевченко (Медицина в Кузбассе, 2016)
Objective – to study the conditions influencing the persistence of B. anthracis in different kinds of soil in permanently anthrax-contaminated areas in the Republic of Altai and the Altai Territory. Materials and methods. We investigated different kinds of soilin two districts in the Republic of Altai and nine districts in the Altai Territory for possible anthrax persistence in the period 2012-2015. In the study 513 samples of different kinds of soil were selected and 1669 laboratory tests were performed using bacteriological, mollecular, genetic and biological methods. Results. The study revealed steppe and forest-steppe in natural and geographical areas of the Altai Territory to provide the predominantly favourable conditions for B. anthracis persistence. During the anthrax epizootic period in 2012 the cultures of anthrax microbe were obtained from the areas of animals death loss. The study showed the higher probability of B. аnthracis persistence in soils of the AltaiTerritory areas than in the Republic of Altai areas. Conclusions. The study showed the higher probability of B. anthracis persistence in soil in areas of the AltaiTerritory than in the Republic of Altai, and therefore, it is in the AltaiTerritorythat the risk of anthrax in animals and humansis greater.